Tecnologías Opacas - Parra Cancino, Juan (2024)
guitar, electronics and networked trumpet
Workshop, lecture, and performance for the faculty and Students of the Universidad Austral of Valdivia, Chile
FRIS
Editorial review
Keywords: Music, Thought and Technology